Diseño de un centro de capacitación y desarrollo agroturístico para la parroquia Angochagua - Ayala Bedon, Emerson Andrés (2024)
The parish of Angochagua is an emerging tourist destination that combines a rich cultural history with stunning natural landscapes. This work focuses on analyzing tourism, gastronomy, agriculture, the textile industry, and livestock farming, and how these sectors combine to foster regional socioeconomic development. In the realm of tourism, the region offers a variety of outdoor activities and historical sites that attract both local and international visitors. This study will examine the impact of tourism on the local economy and cultural preservation, as well as strategies to promote sustainable and responsible tourism. Local gastronomy is a highlight of Angochagua's culture, featuring traditional dishes made with fresh, locally grown ingredients. The impact of gastronomy on the community's cultural identity and its potential as a tourist attraction will be investigated. Agriculture and livestock farming are fundamental pillars of the sector's economy, with a diversified production of crops and livestock. The study will analyze the challenges and opportunities in these sectors, including sustainable agricultural practices and crop diversification. A design proposal for a training and agrotourism development center in the parish of Angochagua aims to enhance training, the economy, and tourism in the sector, as well as support community welfare and progress in the region. Additionally, the architectural project aims to link training and experimentation spaces for the cultivation, breeding, and feeding of animals.